Pengaruh Gaya Kepemimpinan Demokratis, Motivasi Instrinsik dan Stres Kerja terhadap Kinerja Pegawai - Mahardhika, Eggi; Sumartik, Sumartik (Jambura Journal of Educational Management, 2025)
This study aims to find out and measure the influence of transformational leadership style, intrinsic motivation, and work stress on employee performance at PT. Nala Anggada Perkasa. This research includes quantitative research that uses an explanatory research approach. The population in this study was taken from the number of all employees at PT. Nala Anggada Perkasa. The sample obtained amounted to 45 respondents with a total sampling data collection technique. Data collection in this study was by means of observation and distributing questionnaires measured using the Likert scale. This study uses the Structural Equation Modeling (SEM) analysis method. The data analysis technique used in this study uses PLS (Partial Least Square) version 3.0. The results of this study prove that the variational of transformational leadership styles, intrinsic motivation and work stress have a positive and significant influence on employee performance at PT. Nala Anggada Perkasa.